Comparative in vitro genotoxicity study of ZnO nanoparticles, ZnO macroparticles and ZnCl2 to MDCK kidney cells: Size matters. (April 2017) - Kononenko, Veno; Repar, Neža; Marušič, Nika; Drašler, Barbara; Romih, Tea; Hočevar, Samo; Drobne, Damjana
Abstract: In the present study, we evaluated the roles that ZnO particle size and Zn ion release have on cyto- and genotoxicity in vitro . The Madin-Darby canine kidney (MDCK) cells were treated with ZnO nanoparticles (NPs), ZnO macroparticles (MPs), and ZnCl2 as a source of free Zn ions. We first tested cytotoxicity to define sub-cytotoxic exposure concentrations and afterwards we performed alkaline comet and cytokinesis-block micronucleus assays. Additionally, the activities of both catalase (CAT) and glutathione S-transferase (GST) were evaluated in order to examine the potential impairment of cellular stress-defence capacity. The amount of dissolved Zn ions from ZnO NPs in the cell culture medium was evaluated by an optimized voltammetric method. The results showed that all the tested zinc compounds induced similar concentration-dependent cytotoxicity, but only ZnO NPs significantly elevated DNA and chromosomal damage, which was accompanied by a reduction of GST and CAT activity. Although Zn ion release from ZnO NPs in cell culture medium was significant, our results show that this reason alone cannot explain the ZnO genotoxicity seen in this experiment. We discuss that genotoxicity of ZnO NPs depends on the particle size, which determines the physical principles of their dissolution and cellular internalisation. Highlights: ZnO nanoparticles are genotoxic at sub-cytotoxic exposure concentrations. Genotoxicity of ZnO particles depends on the particle size. ZnO genotoxicity cannot be explained by extracellular Zn ion release only. ZnO genotoxicity is accompanied by decreased cellular stress-defence capacity.